Hair Cell Protection from Ototoxic Drugs - Peng Wu; Xianmin Wu; Chunhong Zhang; Xiaoyun Chen; Yideng Huang; He Li (Neural Plasticity)
Hearing loss is often caused by death of sensory hair cells (HCs) in the inner ear. HCs are vulnerable to some ototoxic drugs, such as aminoglycosides(AGs) and the cisplatin.The most predominant form of drug-induced cell death is apoptosis. Many efforts have been made to protect HCs from cell death after ototoxic drug exposure. These mechanisms and potential targets of HCs protection will be discussed in this review.And we also propose further investigation in the field of HCs necrosis and regeneration, as well as future clinical utilization.